Co-valorisation of cassava peel and rice husk to biofuel precursor via intermediate pyrolysis: Kinetics, thermodynamic and pyrolytic oil characterisation - Ezeh Ernest Mbamalu; Isah Yakub Mohammed (Waste Management Bulletin)
This study explored the co-valorisation of cassava peel and rice husk into biofuel precursors through pyrolysis. The research involved characterization of the biomass, and thermogravimetric analysis at heating rates of 5, 10, and 15 °C/min. An intermediate pyrolysis was conducted using a laboratory-scale setup with a stainless-steel reactor and a Swagelok double-ended tube, yielding pyrolytic oil for analysis. Proximate analysis revealed cassava peel (CP) contains 9.23 wt% ash, while rice husk (RH) has 16.50 wt% ash respectively, while the combined samples of cassava peel and rice husk (CS) had ash content of 74.27 wt%, fixed carbon of 70.07 wt%, and volatile matter of 75.72 wt%. The heating values for the samples were 17.15 MJ/kg, 15.22 MJ/kg, and 17.06 MJ/kg for cassava peel, rice husk, and combined sample respectively. Ultimate analysis indicated the following elemental compositions: CP (40.95 % C, 5.67 % H, 0.22 % N, 0.09 % S, 52.17 % O2), RH (40.15 % C, 5.98 % H, 0.41 % N, 0.78 % S, 52.68 % O2), and the CS (43.06 % C, 6.41 % H, 0.32 % N, 0.41 % S, 49.80 % O2). Kinetic and thermodynamic analysis from the distributed activation energy models revealed average activation energies of 184.95 kJ/mol (CP), 140.56 kJ/mol (RH), and 125.63 kJ/mol (CS). The pyrolysis products consist of 37.50 wt% pyrolytic oil, 11.12 wt% bio-char, and 51.38 wt% non-condensable gases. GC–MS analysis of the pyrolytic oil identified significant amounts of hydrocarbons, phenols, and phenol derivatives, suggesting potential for biofuel production. This study highlights the viability of combined biomass sources for biofuel production and waste to wealth utilization.